‘Spanish’ flu and army horses: what historians and biologists can learn from a history of animals with flu during the 1918–1919 influenza pandemic - Haalboom, Floor (Studium, 2014)
At the time of the 1918–1919 ‘Spanish’ influenza pandemic, influenza researchers did not just relate this disease to the human population, despite the focus of historians of medicine on its human aspects and meanings. In line with the use of historical reports of animals with influenza in present-day microbiological studies on influenza among different animal species, this article investigates understandings of animal influenza in the Netherlands during the 1918–1919 pandemic. The article adds to microbiological uses of the historical record by putting observations of animals with influenza in historical contexts, in particular the context of military dealings with influenza at the end of the First World War, and the social position of veterinary medicine. The case of the Dutch military horse veterinarian Emile Bemelmans, who argued that human and horse influenza were identical, illustrates that knowledge of these contexts is important to critically use historical sources reporting animals with influenza in present-day biological influenza research.